2016
DOI: 10.1016/j.hpb.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgery for recurrent pyogenic cholangitis: a single center experience

Abstract: Background: Although, recurrent pyogenic cholangitis (RPC) is prevalent in several parts of India, there

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…3,6 A previous study had reported the left lobe, right lobe and both lobes to be involved in 49%, 13% and 38% respectively, which is similar to that observed in this study. 2 If hepatolithiasis is confined to the left liver, liver resection (left hepatectomy or left lateral segmentectomy) is the best treatment. 4,7 In the present study, it was performed in 33% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,6 A previous study had reported the left lobe, right lobe and both lobes to be involved in 49%, 13% and 38% respectively, which is similar to that observed in this study. 2 If hepatolithiasis is confined to the left liver, liver resection (left hepatectomy or left lateral segmentectomy) is the best treatment. 4,7 In the present study, it was performed in 33% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 If failed, it should be followed by hepatectomy of the severely affected segments, combined with stone removal, ontable choledochoscopic removal of stones from the remnant liver (with laser lithotripsy) and biliary bypass to prevent recurrence. 2,[9][10][11] Biliary bypass (Roux-en-Y hepatico-jejunostomy) facilitates post-operative natural clearance of residual intrahepatic stones. Bilobar disease is categorized as a high grade disease with greater risk of disease recurrence, often requiring multi-modality treatment for optimal management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations